(untitled) (World Bulletin of Social Sciences, 2024)
This article talks about the traditions of our national values, which have been passed down from generation to generation from ancient times to the present day. The traditions of the master-disciple, which have taken a deep place in the art of music, the history of society and the specific aspects of its role in the development of young people, are considered, and their formation over the years is classified